Multiple Mechanisms Increase Levels of Resistance in Rapistrum rugosum to ALS Herbicides - Hatami, Zahra M.; Gherekhloo, Javid; Rojano-Delgado, Antonia M.; Osuna, Maria D.; Alcántara, Ricardo; Fernández, Pablo; Sadeghipour, Hamid R.; De Prado, Rafael (Frontiers in Plant Science, 2016)
Rapistrum rugosum (turnip weed) is a common weed of wheat fields in Iran, which is most often controlled by tribenuron-methyl (TM), a sulfonylurea (SU) belonging to the acetolactate synthase (ALS) inhibiting herbicides group. Several cases of unexplained control failure of R. rugosum by TM have been seen, especially in Golestan province-Iran. Hence, there is lack of research in evaluation of the level of resistance of the R. rugosum populations to TM, using whole plant dose–response and enzyme assays, then investigating some potential resistance mechanisms Results revealed that the resistance factor (RF) for resistant (R) populations was 2.5 to 6.6 fold higher than susceptible (S) plant. Neither foliar retention, nor 14C-TM absorption and translocation were the mechanisms responsible for resistance in turnip weed. Metabolism of TM was the second resistant mechanism in two populations (Ag-R5 and G-1), in which three metabolites were found. The concentration of TM for 50% inhibition of ALS enzyme activity in vitro showed a high level of resistance to the herbicide (resistance factors were from 28 to 38) and cross-resistance to sulfonyl-aminocarbonyl-triazolinone (SCT), pyrimidinyl-thiobenzoate (PTB) and triazolopyrimidine (TP), with no cross-resistance to imidazolinone (IMI). Substitution Pro 197 to Ser 197 provided resistance to four of five ALS-inhibiting herbicides including SU, TP, PTB and SCT with no resistance to IMI. These results documented the first case of R. rugosum resistant population worldwide and demonstrated that both RST and NRST mechanisms are involved to the resistance level to TM.